Familial eruptive vellus hair cysts. - Vassilopoulou, A.; Betto, P.; Germi, L.; Veller Fornasa, C. (European Journal of Pediatric Dermatology, 2011)
Eruptive vellus hair cysts are uncommon development anomalies of vellus hair follicles that usually affect the pediatric population. Rarely they can be seen in adults. This disorder may occur sporadically or may be inherited in an autosomal dominant manner, as was the case with our patients. A 32-years-old black woman and her daughter of 4 years had an extensive asymptomatic yellowish papular skin eruption. A skin biopsy specimen of both patients led to diagnose eruptive vellus hair cysts.